2011
DOI: 10.1177/1947601911423030
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling in Developmental and Tumor Angiogenesis

Abstract: The discovery that Notch, a key regulator of cell fate determination, is functional in the vasculature has greatly improved our understanding of differentiation and specialization of vessels. Notch signaling has been proven to be critical for arterial specification, sprouting angiogenesis, and vessel maturation. In newly forming vascular sprouts, Notch promotes the distinction between the leading "tip" endothelial cell and the growing "stalk" cell, the endothelial cells that eventually form a new capillary. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 131 publications
(194 reference statements)
1
95
0
2
Order By: Relevance
“…Previous studies have proposed that the aberrant activation of the JAG1-Notch1 signaling pathway may protect cancer cells from cisplatin-induced cell apoptosis and that the signaling activity is inversely correlated with the cisplatin sensitivity of human cancers [53-57]. Moreover, Notch signaling is associated with tumor growth and angiogenesis [58, 59]. A recent study has suggested that the modulation of tumor angiogenesis by blocking VEGF signaling could reduce the chemoresistance of ovarian cancer [60], suggesting that JAG1/NOTCH1/neovascularization confers ovarian cancer chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proposed that the aberrant activation of the JAG1-Notch1 signaling pathway may protect cancer cells from cisplatin-induced cell apoptosis and that the signaling activity is inversely correlated with the cisplatin sensitivity of human cancers [53-57]. Moreover, Notch signaling is associated with tumor growth and angiogenesis [58, 59]. A recent study has suggested that the modulation of tumor angiogenesis by blocking VEGF signaling could reduce the chemoresistance of ovarian cancer [60], suggesting that JAG1/NOTCH1/neovascularization confers ovarian cancer chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…The Notch signaling pathway governs cell fate decisions in many tissues via direct cell-cell contact [13,14]. There are four transmembrane receptors (Notch1, 2, 3, 4) that are activated by four ligands [Delta-like (Dll) 1 and 4 and Jagged (Jag) 1 and 2] [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…There are four transmembrane receptors (Notch1, 2, 3, 4) that are activated by four ligands [Delta-like (Dll) 1 and 4 and Jagged (Jag) 1 and 2] [14,15]. Targeted inactivation or overexpression of murine Notch family members results in a variety of vascular defects, commonly causing embryonic lethality [1621].…”
Section: Introductionmentioning
confidence: 99%
“…The best validated tumour angiogenic factor is the glycoprotein vascular endothelial growth factor (VEGF)-A (also known as VEGF or vascular permeability factor) [49], which is induced by hypoxia and induces sprouting and proliferation of blood vascular endothelial cells via VEGF receptor-2 (VEGFR-2), a tyrosine kinase on the surface of these cells [50]. VEGFR-2 activation signals for other facets of angiogenesis such as remodelling of extracellular matrix by matrix metalloproteinases [51] and integrins [52], endothelial cell guidance through semaphorins, ephrins, slits and their cognate receptors [48], through Delta-like 4/Notch signalling [53], and vessel formation and recruitment of pericytes (involving platelet-derived growth factors (PDGFs) [54]) (see [48] for overview). Alternative tumour angiogenic factors have been characterized in animal models, and are expressed in human cancers, including fibroblast growth factors (FGFs) [55], placenta growth factor (PlGF) [56, 57], angiopoietins [58], VEGF-C [59-61] and VEGF-D [62-64].…”
Section: Molecular Mediators Of Cancer Progressionmentioning
confidence: 99%